Genotype x environment interaction for grain yield of maize (Zea mays L.) inbreds under salinity stress (Bangladesh Journal of Agricultural Research, 2014)
An experiment was conducted on Maize (Zea mays L.) to investigate the genotype × environment interaction for gain yield of maize inbreds under salinity stress. The objective of this study was to evaluate G × E interactions and yield stability in multi-environmental trials across wide ecological stress environments. Prescreened thirteen maize inbred lines collected from CYMMT, India were evaluated for phenotypic traits at different salinity conditions (8dS, 12dS and 16dS) with normal environment. The environmental mean and genotypic mean ranged from 10.3 to 49.7 g and 10.9 to 52.8 g, respectively. The regression coefficient (bi) values of these genotypes ranged from 0.44 to 1.66. Among the genotypes P43, CZ29 and CZ33 produced higher grain yield and highly responsive under different salinity level. On the other hand considering the Pi, bi, S2di and AMMI bi-plot analysis the genotypes E32, P29 and P35 showed almost stable performance across the different salinity conditions. DOI: http://dx.doi.org/10.3329/bjar.v39i2.20431 Bangladesh J. Agril. Res. 39(2): 293-301, June 2014